2021
DOI: 10.1172/jci.insight.151463
|View full text |Cite
|
Sign up to set email alerts
|

Airway antibodies emerge according to COVID-19 severity and wane rapidly but reappear after SARS-CoV-2 vaccination

Abstract: Understanding the presence and durability of antibodies against SARS-CoV-2 in the airways is required to provide insights on the ability of individuals to neutralize the virus locally and prevent viral spread. Here, we longitudinally assessed both systemic and airway immune responses upon SARS-CoV-2 infection in a clinically well-characterized cohort of 147 infected individuals representing the full spectrum of COVID-19 severity; from asymptomatic infection to fatal disease. In addition, we evaluated how SARS-… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 62 publications
4
19
0
Order By: Relevance
“…Whilst a Dutch study of healthcare workers found that nasal antibody lasted 9 months after mild infection, others demonstrated rapid waning after 3 months. 8,9 Neither study examined a large cohort of hospitalised patients, and our findings confirm that COVID-19 can induce durable mucosal immunity. We also found that disease severity and age did not impact the longevity of the nasal responses in keeping with a recent study of 26 unvaccinated individuals.…”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…Whilst a Dutch study of healthcare workers found that nasal antibody lasted 9 months after mild infection, others demonstrated rapid waning after 3 months. 8,9 Neither study examined a large cohort of hospitalised patients, and our findings confirm that COVID-19 can induce durable mucosal immunity. We also found that disease severity and age did not impact the longevity of the nasal responses in keeping with a recent study of 26 unvaccinated individuals.…”
Section: Discussionsupporting
confidence: 65%
“…vaccination, highlighting that an independent response must occur at mucosal sites. 9,27 Moreover, previous work has demonstrated that transudation of plasma antibody makes minimal contribution to total antibody concentrations in the mucosa, even in cases of paraproteinaemia where plasma concentrations are extremely high. 28 This would explain why i.m.…”
Section: Discussionmentioning
confidence: 99%
“…In paired sampling of nasopharyngeal (NP) samples and plasma, anti‐S and RBD antibody levels in NP samples correlated with levels in plasma, were mostly IgA, and were increased in severe compared with mild‐or‐moderate COVID‐19. 75 Antibodies in the respiratory tract further correlated with the presence of virus‐specific B‐cells and lower viral load, 75 , 76 indicating potential protective capacity of these locally produced antibodies through direct neutralization or targeting the virus for clearance by innate cells.…”
Section: Site‐specific and Systemic Immune Responses During Acute Inf...mentioning
confidence: 99%
“…Memory B‐cells residing in lymph nodes may be sufficient for rapid mobilization of humoral immunity, even if the levels of antibody maintained in circulation decline. For local antibody‐mediated protection, there is evidence for maintenance of IgA antibodies in the nasal passages, 74 though the longevity of mucosal IgA is variable 75 and their ability to block local infection is not known.…”
Section: Immune Correlates Of Protection Generated By Sars‐cov‐2 Infe...mentioning
confidence: 99%
“… To the Editor: Mucosal IgA can provide immunity against respiratory viruses. 1 Vaccination against severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) boosts mucosal IgA responses, 2 and neutralizing IgA, including neutralizing IgA against the B.1.1.529 (omicron) variant of SARS-CoV-2, has been detected after infection with wild-type SARS-CoV-2. 3 However, the potential role of mucosal IgA in protection against SARS-CoV-2 infection is still largely unknown.…”
mentioning
confidence: 99%